Using an Experimental Framework to Support Variables Selection: An Exploratory Study - Scatalon, Lilian Passos; Garcia, Rogério Eduardo [UNESP]; Barbosa, Ellen Francine (World Scientific Publishing, 2021)
The selection of variables in a given experiment is crucial, since it is the theoretical foundation that guides how data should be collected and analyzed. However, selecting variables is an intricate activity, especially considering areas such as Software Engineering and Education, whose studies should also consider human-related variables in the design. In this scenario, we aim to investigate how a support mechanism helps in the variables selection activity of the experiment process. To do so, we conducted a preliminary study on the use of an experimental framework composed of a catalog of variables. We explored the domain of the integration of software testing into programming education. Participants were divided into two groups (ad hoc and framework support) and asked to select variables for a given experiment goal. We analyzed the results by identifying threats to validity in their experimental design drafts. Results show a significant number of threats of type inadequate explication of constructs for both groups. Nonetheless, the framework helped to increase the clarity of concepts selected as variables. The cause of most raised threats, even with the framework support, was an inaccuracy in selecting the values of such variables (i.e. treatments and fixed values).
Keywords: Experimental design; experimental framework; support mechanisms; variables selection